Does Religious Faith Matter in Development Practice? Perspectives from the Savelugu-Nanton District in Northern Ghana. Issue 2 (3rd May 2020) - Dotsey, Senyo; Kumi, Emmanuel
Abstract: Religious faith and its role in development policy and practice has received much attention in recent years. However, there is relatively limited knowledge of how Christian faith is manifested in the day-to-day administration of non-governmental organisations (NGOs) and how that shapes their relationships with intended beneficiaries in a Muslim-dominated community. This article addresses the knowledge gap by examining how the Christian identity of World Vision Ghana (WVG) and the 'religious lifeworlds' of employees and the extent to which these shape their development interventions in Northern Ghana. Using a qualitative research approach, we found that religious faith and beliefs play a key role in WVG employees' daily administrative activities and field operations, with the employees often perceiving development as a religious act. We argue that in an attempt to promote 'holistic development', WVG employees draw on lifestyle evangelism and community structures to promote their Christian values in a multi-faith environment with Muslim dominance. In doing so, we show how the religious configuration of Muslim-dominated communities creates challenges for Christian NGOs in their attempt to promote holistic development. The implications of the research findings are discussed.